Christy Ng Shoes / Nurhuda Huraiyah Abd Rashid - Abd Rashid, Nurhuda Huraiyah (2020)
The intention of case study is to generate many ideas of this assignment project and learn more about entrepreneurship. I choose to pick a Christy Ng Shoes company for this case study as I felt like it was really inspiring not only me but all of people out there. I feel so glad to do the background and all the requirements of this case study towards the company because it contains a huge impact for me as a student to be a successful entrepreneur in future. The report contains the introduction of Christy Ng Shoes which includes background, business description and entrepreneurial characteristic. Next, it’s also explain about the company and the founder itself for the struggles and problems that she faced throughout the business going from the start until today. Besides, this report also has the articles that she was featured in along with her most inspiring story. Last but not least, there are also the interviews of them from internet sources that was included in this report.